Analisis Kemampuan Berpikir Kritis Siswa Pada Materi Dinamika Rotasi dan Keseimbangan Benda Tegar di SMAN 7 Kota Bengkulu - Nainggolan, Sonya Senita; Putri Johan, Desy Hanisa; Purwanto, Andik (Universitas PGRI Semarang, 2023)
This study aims to determine the critical thinking skills of SMAN 7 Bengkulu City students in solving test questions. This type of research is descriptive using six indicators of critical thinking skills, namely focus, reason, inference, situation, clarity, overview. The subjects involved in this study were 32 students of class XI IPA 4 as many as 32 people. The results of data analysis are: 49.13% of the focus aspect is categorized as low critical thinking ability, R (Reason) is 49.48% categorized as low critical thinking ability, I (Inference) 50.26% is categorized as low critical thinking ability , S (Situation) is 46.79% categorized as low critical thinking ability, C (Clarity) 47.74% is categorized as low critical thinking ability and O (Overview) 44.79% is categorized as low critical thinking ability. So, the results of this study indicate that the critical thinking ability of students at SMAN 7 Bengkulu City is still low. The implications will cause a domino effect for subsequent subjects. Because students only memorize without mastering the subject matter, the next material will be very difficult. Because as the material continues, the level of complexity will be higher.Keywords: analysis, critical thinking skill.Â